Stunting Determinants Among Indonesian Children Aged 0-59 Month: Evidence From Indonesian Family Life Survey (IFLS) 2014/2015 - Eka Mishbahatul Marah Has (Journal of Global Pharma Technology, 2020)
This study aimed to analyze the determinants of stunting among children aged 0-59 months old in Indonesia. A cross-sectional survey by using data from the Indonesian Family Life Survey period 2014/2015 (IFLS-5) was conducted, which focused on the household with children aged 0-59 months old (n=3623). Ordinal regression test showed that determinants of stunting among children aged 0-59 months old, consist of children aged <6 and 6-23 months old; male; low birth weight; underweight mother; normal height mother; poor household; and ever had antenatal care. Integrated intervention address children, mother, and health service factors associated with stunting is needed.Keywords: Children, Indonesian family life survey, Stunting.